Unexploited profit among smallholder farmers in central Malawi: what are the sources? - Assa, M.M.; Edriss, A.K.; Matchaya, Greenwell C. (2012)
The purposes of this research were to measure the profit efficiency of sample Irish potato farms and subsequently to explore determinants of profit inefficiency in the Dedza district of Malawi. Flexible Stochastic Profit Frontier Analysis was used to measure profit efficiency. Farmers from 200 randomly selected farmers were interviewed for plot level data. Research results revealed that the average profit of Irish potato farmers in Dedza could increase by 26% under prevailing technology. The profit efficiency of the sample Irish potato farms ranged from 0.31 to 0.99 (0.74 average). Policy variables like non-farm employment, education, extension visits, credit status, farm Experience, degree of specialization, and frequency of weeding negatively affected profit inefficiency. Conversely, age affected profit inefficiency positively.